Teaching literary elements : easy strategies and activities to help kids explore and enrich their experiences with literature - McCarthy, Tara (New York : Scholastic Professional Books, 1997)
Teaching activities and reproducible pages on basic elements that go into all good stories (character, setting, plot, conflict, climax, resolution, imagery, dialogue), readers understand how each of these elements develops and builds upon others as a story evolves
Includes bibliography
"Grades 4-8"--Cover
Keywords: Literature -- Study and teaching (Elementary); Reader-response criticism; Literary form -- Study and teaching (Elementary)